Application of the Six Sigma Method in Knowing the Level of Student Satisfaction with the Learning System in Schools - Roni Ardiwan; Leni Natalia Zulita; Jhoanne Fredricka (Penerbit Jurnal Indonesia, 2021)
SMA Negeri 4 Bengkulu Tengah is one of the state high schools located in Bengkulu Tengah Regency, Bengkulu Province. SMA Negeri 4 Bengkulu Tengah does not yet have a system that can be used to measure the level of student satisfaction with the learning system in schools, so there is no parameter for the level of student satisfaction. This results in the school not having a benchmark in knowing and evaluating the learning system that is currently being carried out. This impact makes it difficult for schools to improve the learning system in schools. The application of the level of student satisfaction with the learning system at SMA Negeri 4 Bengkulu Tengah Regency was made using the Visual Basic programming language. Net with SQL Server 2008r2 database, where the application has been applied to the Six Sigma method in analyzing the level of student satisfaction. The application of the level of student satisfaction with the learning system at SMA Negeri 4 Bengkulu Tengah Regency is able to facilitate students in providing an assessment of student satisfaction, and also makes it easier for the school to determine the level of student satisfaction with the learning system at school. In the application of the level of student satisfaction with the learning system at SMA Negeri 4 Bengkulu Tengah Regency, there are 2 access rights granted, namely Administrator and Student. To enter the administrator's main menu page and the student's main menu, the user must first log in. Based on the blackbox testing that has been carried out, the functional application of the level of student satisfaction with the learning system at SMA Negeri 4 Bengkulu Tengah Regency can run as expected in terms of data input, analysis and print report output.